Gastrointestinal manifestations of COVID-19-associated multisystem inflammatory response syndrome in children - Avramenko І. Yu.; Kosmynina, N. S.; Pidvalna, U. Ye.; Basa, N. R. (Zaporozhye Medical Journal, 2022)
Aim: analysis of the course of SARS-Cov-2-associated multisystem inflammatory response syndrome (MIS-C) with gastrointestinal disorders in comparison with MIS-C without gastrointestinal manifestations in children of the Lviv region. Materials and methods. Analysis of medical records of children under the age of 15 years who were treated at the CNE LRC LRCCH “ОHMATDYТ” with a diagnosis of MIS-C associated with SARS-Cov-2. Results. Gastrointestinal manifestations of MIS-C associated with SARS-Cov-2 were observed in 52.38 % of children, and other symptoms in this group of patients included headache and cough. Levels of specific SARS-Cov-2 IgG did not differ significantly in children with and without gastrointestinal symptoms. In contrast, patients with MIS-C without gastrointestinal manifestations were more likely to have myocardial dysfunction, requiring longer hospitalization. Children with gastrointestinal manifestations of MIS-C were more likely to be obese. Conclusions. The severity of the clinical course of multi-inflammatory systemic response syndrome associated with SARS-Cov-2 did not depend on the severity and time elapsed since acute coronavirus disease and was not associated with gastrointestinal manifestations, which were observed in 52.38 % of patients. Cough and headache, even in the absence of such typical MIS-C manifestations as rash, scleral changes and swelling of the extremities, could be symptoms allowing a surgeon to think about conservative management of a patient with acute abdominal syndrome. MIS-C associated with SARS-Cov-2 should be included in clinical protocol guiding management of acute appendicitis in children.